The effect of pyrogens on interleukin 6 (IL-6) secretion by whole blood cultures - Pool, E. J.(Edmund John) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Pd.D. in Medical Microbiology) -- University of Stellenbosch, 1999.